2013
DOI: 10.1039/c3fo60221d
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, antibacterial and ACE-inhibitory activity of four monofloral honeys in relation to their chemical composition

Abstract: Different monofloral honeys from Castilla-La Mancha (Spain) have been studied in order to determine their main functional and biological properties. Thyme honey and chestnut honey possess the highest antioxidant capacity, which is due to their high vitamin C (in thyme honey) and total polyphenolic content (in chestnut honey). On the other hand, chestnut honey showed high antimicrobial activity against Staphylococcus aureus and Escherichia coli, whilst others had no activity against S. aureus and showed very sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 41 publications
2
22
0
Order By: Relevance
“…Our results agreed with literature, because a previous study carried out on Tunisian propolis also showed an ACE inhibition higher than 90% [17]. In comparison with other products, propolis exhibited a considerably higher ACE-inhibitory activity percentage, because values obtained for fermented milk (20-90%) [22], honeys at 50% (17-71%) [53], Echium vulgare honeys at 50% (94.2%) [54], mung bean and rice protein hydrolysates (52-96%) [55] as well as Ramie (Boehmeria nivea Gaudich) leaves extracts (51% inhibition) [56], were considerably lower. Therefore, the use of propolis could modulate the ACE, providing an effective control of hypertension, which is an important strategy to decrease the risk for cardiovascular diseases.…”
Section: Ace Inhibitory Activitysupporting
confidence: 91%
See 1 more Smart Citation
“…Our results agreed with literature, because a previous study carried out on Tunisian propolis also showed an ACE inhibition higher than 90% [17]. In comparison with other products, propolis exhibited a considerably higher ACE-inhibitory activity percentage, because values obtained for fermented milk (20-90%) [22], honeys at 50% (17-71%) [53], Echium vulgare honeys at 50% (94.2%) [54], mung bean and rice protein hydrolysates (52-96%) [55] as well as Ramie (Boehmeria nivea Gaudich) leaves extracts (51% inhibition) [56], were considerably lower. Therefore, the use of propolis could modulate the ACE, providing an effective control of hypertension, which is an important strategy to decrease the risk for cardiovascular diseases.…”
Section: Ace Inhibitory Activitysupporting
confidence: 91%
“…Samples with different polyphenols' concentrations showed an almost equal hyaluronidase inhibitory activity, suggesting that these compounds were not the unique factors responsible for this activity [51]. As for ACE inhibitory activity, in a previous study carried out on honeys no significant correlations were observed between ACE inhibitory activity and phenols or antioxidant capacity [53]. In our research on propolis, ACE inhibitory activity was negatively correlated with total flavones/flavonols (r = −0.5451) and total flavanones/dihydroflavonols (r = −0.5540) and positively correlated with flavanols (r = 0.3766), catechin (r = 0.6096) and p-coumaric acid (r = 0.5575).…”
Section: Correlationsmentioning
confidence: 89%
“…Both low and high molecular weight ACE inhibitors were shown in the rat lung [33] or in the human sera [58]. Peptides of the tryptic lysate of human plasma [35], [36], human serum albumin [59], bovine alphaS2-casein [43] and some types of honey were also found to inhibit ACE [41].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of honey, additional antimicrobial agents may be present, such as peroxides and nonperoxide compounds . However, the concentration of these chemical species varies widely with honey type and origin …”
Section: Discussionmentioning
confidence: 99%